Comparative analysis of AAV serotypes for transduction of olfactory sensory neurons - Benjamin D. W. Belfort; Benjamin D. W. Belfort; Benjamin D. W. Belfort; Benjamin D. W. Belfort; Benjamin D. W. Belfort; Johnathan D. Jia; Johnathan D. Jia; Johnathan D. Jia; Alexandra R. Garza; Alexandra R. Garza; Alexandra R. Garza; Alexandra R. Garza; et al. (Frontiers in Neuroscience)
Olfactory sensory neurons within the nasal epithelium detect volatile odorants and relay odor information to the central nervous system. Unlike other sensory inputs, olfactory sensory neurons interface with the external environment and project their axons directly into the central nervous system. The use of adeno-associated viruses to target these neurons has garnered interest for applications in gene therapy, probing olfactory sensory neuron biology, and modeling disease. To date, there is no consensus on the optimal AAV serotype for efficient and selective transduction of olfactory sensory neurons in vivo. Here we utilized serial confocal imaging and single-nucleus RNA sequencing to evaluate the efficacy of 11 different AAV serotypes in transducing murine olfactory sensory neurons via non-invasive nasal inoculation. Our results reveal that AAV1, while highly effective, exhibited broad tropism, whereas AAV-DJ/8 showed the greatest specificity for olfactory sensory neurons.